Rheology and processing study on controlling material and process defects in polymer melt extrusion film casting using polymer blends - Rokade, Dhammaraj; Patil, Prashant; Nandimath, Sheetal; Pol, Harshawardhan (Journal of Plastic Film & Sheeting, 2023)
The primary objective of this research paper is to control the material and process defects in polymer melt extrusion film casting (EFC) process for linear chain architecture polyethylene (PE) resins through polymer blending methodology. Extrusion film casting is a well-known industrially important manufacturing process that is used to manufacture thousands of tons of polymer/plastic films/sheets and coated products. In this research, the necking defect in an EFC process has been studied experimentally for a linear low density polyethylene (LLDPE) resin and attempts have been made to control its necking by blending in a long chain branched (LCB) low density polyethylene (LDPE) resin. The blending methodology is based on the understanding that a LDPE resin displays enhanced resistance to necking as compared to the LLDPE resin. It is found that added LDPE resin enhances necking resistance for the primary LLDPE resin. Further, as the LDPE concentration increases in the blend formulation, the necking is further reduced as compared to pure LLDPE. Analogous to past studies on EFC of linear and long chain branched architecture containing PEs, it is observed that as the LDPE is increased in the blend formulations, the formulations displayed enhanced melt elasticity and extensional strain hardening in rheological studies. It is concluded from this study that polyethylene resins having linear chain architecture can be made amenable to enhanced resistance to necking using appropriate amount of a long chain branched resins. Finally, process defects such as the draw resonance onset could be shifted to higher draw ratios as the LDPE level is increased in the LLDPE-LDPE blend formulation.
Keywords: Draw resonance; Extrusion; Film; linear chain; long-chain branched; melt elasticity; Necking; onset; strain hardening